Performance characteristics of a passive direct formate fuel cell. (13th August 2019) - Su, Xiangyu; Pan, Zhefei; An, Liang
Summary: A passive direct formate fuel cell using ambient air is designed, fabricated, and tested. This fuel cell does not use any auxiliary devices such as pumps, gas compressors, and gas blowers. The simple and compact structure well fits the need of portable applications. In this fuel cell, a solution having formate and alkali is anode fuel, while ambient oxygen is used as cathode oxidant, and a cation exchange membrane serves as an ionic conductor between two electrodes. Our performance tests have shown that a peak power density of 16.6 mW cm −2 as well as an open‐circuit voltage of 0.97 V are achieved by the present fuel cell at 60 °C, when running on anode fuel containing 5.0 M sodium formate and 3.0 M sodium hydroxide. This performance is even 31.7% higher than that achieved by an active direct formate fuel cell reported in the open literature (12.6 mW cm −2 ), which also uses a cation exchange membrane. The effects of the operating parameters are also investigated, including the concentrations of fuel and alkali as well as the operating temperature. The fuel solution at low concentrations results in an inadequate local concentration of reactants, so that the anodic kinetics becomes sluggish. Although increasing the sodium hydroxide concentration enhances the anodic formate oxidation kinetics, too high concentration of sodium hydroxide leads to too many active sites being covered by hydroxide ions and thus adsorption and reaction of formate ions being limited. Moreover, too high concentration of sodium hydroxide or sodium formate also leads to the fuel solution being highly viscous, hindering the motion of various ions, as well as thus increasing both concentration loss and the ohmic loss. The compromise between benefits and the drawbacks of using high‐concentration reactants results in an optimal composition of the fuel solution, which contains 5.0 M sodium formate and 3.0 M sodium hydroxide. Furthermore, the present fuel cell delivers a voltage around 0.6 V for 20 hours at 4.0 mA cm −2 . Abstract :